The investigation of genetic polymorphisms in the carbonic anhydrase VI gene exon 2 and salivary parameters in type 2 diabetic patients and healthy adults - YARAT, AYŞEN; ULUCAN, KORKUT; AKYÜZ, SERAP HATİCE (SPRINGER, 2012)
The aim of this study was to investigate carbonic anhydrase (CA) VI Exon 2 single nucleotide polymorphism (SNP) and its possible association with salivary parameters in type 2 diabetic patients compared to healthy adults. Caries status was measured by using the DMFT (number of decayed, missing, and filled teeth) index. Unstimulated whole saliva and blood samples were taken. SNPs of CA gene exon 2 were determined by PCR and DNA sequencing. Salivary CA activity and buffering capacity were determined by the method of Verpoorte and Ericson, respectively. Furthermore, salivary pH was measured with pH paper and salivary flow rate was calculated. Salivary buffering capacity and pH were significantly lower in diabetic patients than those of healthy subjects (P < 0.05). Salivary flow rate, CA activity and DMFT levels did not differ between groups (P > 0.05). Four SNPs were detected; their pubmed database number are rs2274327 (C/T), rs2274328 (A/C), rs2274329 (G/C) and rs2274330. While first three of those were responsible for amino acid changes, the last one was not. The frequencies of SNPs were not significant between groups (P > 0.05). Positive significant correlation was found between CA activity and the frequency of SNPs. There was no correlation between the SNPs frequencies and pH or buffering capacity. SNPs found in this study may be related to salivary CA activity in diabetics.
Keywords: Type 2 diabetes; Saliva; Carbonic anhydrase VI; Gene; Polymorphism; ISOENZYME-VI; SUBMANDIBULAR-GLANDS; BUFFER CAPACITY; DENTAL-CARIES; FLOW-RATE; CA VI; MELLITUS; ASSOCIATION